Karen Tuttle's Coordination applied to the performance and interpretation of Edino Krieger's Brasiliana - Piermartiri, Leonardo; Gerling, Daphne Capparelli (Revista Vórtex, 2021)
In challenging SPITZER’s (2009) proposition of absence of structure and balance (parataxis) within “Von deiner Güt’, o Herr und Gott”, from J. Haydn’s The Creation, the present a This article focuses on the application of Coordination, a set of principles and techniques developed by the late violist Karen Tuttle, as applied to the performance of Brasiliana for Viola and Strings by Edino Krieger. Coordination occurs in performance through specific physical motions of the performer’s body that connect the emotional and musical aspects of the interpretation. This study draws on interview content with Dr. Susan Dubois, Tuttle’s former teaching assistant at the Juilliard School of Music, and a leading exponent of her teaching. After a brief background on Tuttle ́s techniques and on the piece itself, annotated excerpts of the solo viola part are provided, with suggested interpretative markings applying these techniques. Article addresses contemporary analytical theories of form that may reveal exactly the opposite. The analytical framework used in the study was drawn from theoretical tools designed by CAPLIN (1998; 2001; 2009), HEPOKOSKI, and DARCY (2006) for the analysis of Classical form. This paper argues that tonal balance is a fundamental organizational device and serves as a structuring agent in the composition discussed. Moreover, the tonal balance featured in “Von deiner Güt’” illuminates the underlying structure of the textual narrative, thus rendering a stronger rhetorical appeal to the climactic moment in which it is inserted. The most salient significance of this research lies in its applicability to other cases of less strict formal structure that may be dismissed as parataxis while they, in fact, feature careful formal construction on the composer’s part.